Odpowiedzi

2010-03-18T23:56:19+01:00
(x-3)^2-16=0 <=> x^2-6x+9-16=0 <=> x^2-6x-7=0

delta=36-4*1*(-7)=64
pierwiastek z delta=8
x1=(6-8)/2=-2/2=-1
x2=(6+8)/2=14/2=7

Odp: x=-1 lub x=7
2010-03-18T23:58:17+01:00
(x-3)²-16=0
x²-6x+9-16=0
x²-6x-7=0
liczymy delte
Δ=b²-4ac
Δ=(-6)²-4*1*(-7)
Δ=36+28
Δ=64
√Δ=8
x₁=-b-√Δ/ 2a
x₁=6-8/ 2*1
x₁=-2/2
x₁=-1

x₂=-b+√Δ/ 2a
x₂=6+8/ 2*1
x₂=14/2
x₂=7
2010-03-18T23:58:19+01:00
(x-3)^2-16=0
x^2 -6x +9 -16=0
x^2 -6x -7 =0
delta = b^2 -4ac
delta = 36 - 4*1*(-7) = 64
delta= 8

X1 = (-b- delta)/ 2a
x1 = (6 - 8)/2
x1= -2/2
x1 = -1

x2 = (-b+ delta)/2a
x2= (6+8)/2
x2 = 14:2
x2= 7